Excitation of \((1s2s)\) \(^{1}S\), the Singlet State of Helium Atoms by Positron Impact - Bhatia, A. K. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2025)
The excitation of the \((1s2s)\) \({}^{1}S\) state of a helium atom has been calculated using scattering functions obtained by the method of polarized orbitals. In this method, the distortion of each orbital is considered due to the presence of the incident particle. The distortion takes place only when the incident particle is outside the target orbital. This method has been widely used in the scattering of electrons and positrons from various targets. Plane-wave normalization of the continuum function is considered, while it has been neglected in calculations carried out by Mandal et al. [1], and Willis and McDowell [3]. Consequently, the present results are higher than those obtained by them.